2019
DOI: 10.1002/ece3.4985
|View full text |Cite
|
Sign up to set email alerts
|

Invasion genetics from eDNA and thousands of larvae: A targeted metabarcoding assay that distinguishes species and population variation of zebra and quagga mussels

Abstract: Identifying species and population genetic compositions of biological invasions at early life stages and/or from environmental (e)DNA using targeted high‐throughput sequencing (HTS) metabarcode assays offers powerful and cost‐effective means for early detection, analysis of spread patterns, and evaluating population changes. The present study develops, tests, and applies this method with a targeted sequence assay designed to simultaneously identify and distinguish between the closely related invasive Eurasian … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(56 citation statements)
references
References 74 publications
2
53
1
Order By: Relevance
“…Our targeted metabarcoding HTS assay could be applied en masse to analyzing eDNA from water or entire plankton samples from net tows (i.e., discerning early life stages of eggs and larvae) to detect new occurrences and dispersal patterns by managers. A targeted assay designed by our laboratory to be specific for the two species of invasive dreissenid mussels, distinguishing between them and many of their haplotypes, has been successfully deployed to simultaneously analyze tens of thousands of veliger larvae to species and population levels from net tows, as well as eDNA water samples [129].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our targeted metabarcoding HTS assay could be applied en masse to analyzing eDNA from water or entire plankton samples from net tows (i.e., discerning early life stages of eggs and larvae) to detect new occurrences and dispersal patterns by managers. A targeted assay designed by our laboratory to be specific for the two species of invasive dreissenid mussels, distinguishing between them and many of their haplotypes, has been successfully deployed to simultaneously analyze tens of thousands of veliger larvae to species and population levels from net tows, as well as eDNA water samples [129].…”
Section: Discussionmentioning
confidence: 99%
“…The ruffe exhibited limited genetic diversity and some population divergence across its 30 year history in the upper Great Lakes, revealing founder effect attributable to a single European source area; it has declined in effective population size and numbers in recent years [6]. In comparison, the zebra mussel’s genetic composition has changed over its three decades in the Hudson River, experiencing several population turn-overs and recolonizations [15, 16], yet has remained consistent in Lake Erie throughout [15, 129]. Some invasions possessed little population genetic structure across their ranges; for example, colonization by Virginia’s warbler Oreothlypis virginiae (Baird, 1860) of the Black Hills in South Dakota showed no differentiation, implicating high gene flow and dispersal [130].…”
Section: Discussionmentioning
confidence: 99%
“…For example, early detection of mosquito vectors using water sample eDNA presented a comparable or higher detection probability to traditional surveys (Schneider et al ., ; Boerlijst et al ., ). There have also been some attempts at using DNA metabarcoding to conduct population genetics studies (Elbrecht et al ., ; Marshall & Stepien, ). However, metabarcoding‐based genotyping shows at least as many experimental biases as DNA metabarcoding for species identification, and is prone to the recovery of erroneous haplotypes (Elbrecht et al ., ).…”
Section: Future Research and Challengesmentioning
confidence: 99%
“…Baker et al () applied droplet digital PCR, also targeting the D‐loop region, to distinguish between different ecotypes of Orcinus orca (Linnaeus, ) (killer whale) (Table ), and found that eDNA results were consistent with hydrophone recordings and visual observations. Most recently, Stepien et al () applied a marker in the mtDNA cytochrome b (Cyt b ) gene to distinguish between specific haplotypes of the invasive Hypophthalmichthys molitrix (Valenciennes, ) (silver carp), while Marshall and Stepien () used a region of the mtDNA cytochrome c oxidase I (COI) gene to distinguish between different haplotypes within the invasive mussel species Dreissena polymorpha (Pallas ()) (European zebra mussel) and D. rostriformis (Deshayes, ) (quagga mussel) (Table ). Stat et al () obtained information on intraspecific diversity within fish species of the genus Lethrinus through metabarcoding of the mitochondrial large ribosomal subunit (16S) gene of fishes (Table ).…”
Section: Population Genetic Studies Based On Environmental Dnamentioning
confidence: 99%